Screening for Novel Membrane Markers of Adult Hippocampal Neurogenesis - Tiwari, Nikita (My University, 2018)
Neurogenesis occurs in the hippocampus throughout adult life both in humans and in rodents. Adult hippocampal neurogenesis (AHN) contributes to memory processes and mood. Neurological disorders such as anxiety and depression are associated with reduced neurogenesis. To evaluate the relevance of neurogenesis to a disease state, we require a technique to monitor neurogenesis in-situ in humans. Hence, we need to identify suitable membrane markers of AHN and develop ligands that will cross the blood-brain barrier (BBB). Until now, membrane markers for hippocampal neurogenesis have been largely lacking, although cytosolic and nuclear markers are known. This project sets out to (i) identify novel membrane markers of AHN and (ii) develop BBB-crossing mini-antibodies (humanized scFv) against these markers. Differential mass spectrometry was used to identify membrane proteins that were expressed in neurogenic competent young rats with elevated AHN (2 months old), but absent in old rats (1-year-old) that are neurogenic incompetent. This yielded a list of 10 candidate proteins that were prioritized for validation using immunohistochemistry. Staining protocols were optimized for each antibody. Validation by immunoblotting hippocampal lysates was also performed. We validated four membrane proteins as positive markers for the neurogenic niche and optimized staining for the BBB-crossing scFv. The next step is to evaluate how efficiently these scFv antibodies transit the BBB in mice following injection to the periphery. This new information and optimized scFv tools will help us to investigate neurogenic changes in rodents and eventually in humans leading to improved diagnosis and ultimately treatment of neuro-psychiatric conditions.
Keywords: Adult Hippocampal Neurogenesis, membrane markers, blood-brain barrier, mass spectrometry, immunohistochemistry, scFv